ENT 530 Business Model Canvas: Doorgiftmurahlah / Muhammad Daniel Abdul Razak ... [et al.] - Abdul Razak, Muhammad Daniel; Mohamad Zainuddin, Muhammad Faiz; Zainol, Mohamad Zakaria; Zulkiffly, Nur Alya Wahida; Jaafar, Nur Salsabila; Razimi, Nur Shahirah Puteri; Kamarudin, Nuryanti; Kamarudzaman, Siti Ayuni (2021)
Doorgiftmurahlah is a business that produce delicious snacks that meet with the customer’s taste. There are variety of products that Doorgiftmurahlah provide, for example cookies and popcorn. Other than snacks, Doorgiftmurahlah also provide door gift product to their customers. The price for each of the product are cost-effective and they have a good quality product which it helps to attract customer. According to this report, we have included a brief introduction about Doorgiftmurahlah background. Then it followed with the purpose of the Business Model Canvas where we will explain more on their Business Model Canvas elements. Lastly, we will give a conclusion about the report and provide recommendations and also improvements that this business can do to improve their business in the future. The purpose of making this report is to identify how their Business Model Canvas are built. As we have made a research and an interview with the owner of the business, we are able to fill all of the category in the Business Model Canvas such as customer segmentation, value propositions, channels, customer relationships, revenue streams, key activities, key resources, key partnership, and cost structure. To sum everything up, we hope this report can give a complete idea on how this business makes their Business Model Canvas.